2017
DOI: 10.3758/s13423-017-1291-y
|View full text |Cite
|
Sign up to set email alerts
|

Less approach, more avoidance: Response inhibition has motivational consequences for sexual stimuli that reflect changes in affective value not a lingering global brake on behavior

Abstract: Response inhibition negatively impacts subsequent hedonic evaluations of motivationally relevant stimuli and reduces the behavioral incentive to seek and obtain such items. Here we expand the investigation of the motivational consequences of inhibition by presenting sexually appealing and nonappealing images in a go/no-go task and a subsequent image-viewing task. Each initially obscured image in the viewing task could either be made more visible or less visible by repeatedly pressing different keys. Fewer key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…This is important in the social domain because eliciting negative affect in others makes people susceptible to social exclusion (e.g., Driscoll, Barclay & Fenske, 2017). Indeed, we have shown that prior inhibition associated with images of previously-unfamiliar people negatively biases evaluative choices away from those individuals (Fenske et al, 2005) and both reduces behavioural approach toward associated social stimuli (Ferrey et al, 2012;Driscoll et al, 2018) and increases behavioural avoidance of them (Driscoll et al, 2018).…”
Section: Response Inhibition Negatively Impacts Social-emotional Evaluations Of Specific Individualsmentioning
confidence: 88%
See 3 more Smart Citations
“…This is important in the social domain because eliciting negative affect in others makes people susceptible to social exclusion (e.g., Driscoll, Barclay & Fenske, 2017). Indeed, we have shown that prior inhibition associated with images of previously-unfamiliar people negatively biases evaluative choices away from those individuals (Fenske et al, 2005) and both reduces behavioural approach toward associated social stimuli (Ferrey et al, 2012;Driscoll et al, 2018) and increases behavioural avoidance of them (Driscoll et al, 2018).…”
Section: Response Inhibition Negatively Impacts Social-emotional Evaluations Of Specific Individualsmentioning
confidence: 88%
“…Ignoring or withholding motor-responses from face or whole-body images of unfamiliar people can negatively impact subsequent social evaluations of those people, an effect attributed to the propensity of inhibition to affectively devalue associated stimuli (Dickert & Slovic, 2013;Doallo et al, 2012;Driscoll et al, 2018;Fenske et al, 2005;Ferrey et al, 2012;Frischen et al, 2012;Goolsby, Shapiro, Silvert et al, 2009;Kiss et al, 2008;Martiny-Huenger et al, 2014;Raymond et al, 2005). However, because prior studies have so-far only ever utilized attentional-or response-inhibition tasks (e.g., attention: visual search; response: Go/No-go) that require category-level discrimination of the to-be-ignored/no-response items from the targets of attention/response, it has remained unclear whether inhibition and the corresponding social devaluation is solely triggered and associated with category-level representations of the to-be-ignored/no-response individuals according to their membership in a particular socially-relevant group or a shared perceptual feature, or can also be mediated by itemlevel representations in memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with evidence that conflict between competing stimulus/response representations elicits negative affect and thereby leads to more negative evaluations of associated stimuli (Damen et al, 2018;Fritz & Dreisbach, 2013;Goller et al, 2019), it makes sense that researchers (e.g., Chetverikov & Kristjansson, 2015; would question whether stimulusdevaluation effects previously attributed to the affective consequences of inhibition are instead due to the emotional impact of conflict. Resolving whether inhibition has negative affective consequences that exceed any emotional impact of conflict is therefore important for the interpretation of a large and growing corpus of findings that have been thought to reflect stimulus devaluation by inhibition (e.g., Chen, Veling, Dijksterhuis, & Holland, 2016;Chen, Holland, Quandt, Dijksterhuis, & Veling, 2019;Clancy et al, 2019;Driscoll et al, 2018;Fenske et al, 2004;2005;Frischen et al, 2012;Goolsby et al, 2009;Houben et al, 2012;Kihara et al, 2011;Kiss et al, 2007;Martiny-Huenger et al, 2014;Raymond et al, 2003;2005;Vivas et al, 2016;Veling et al, 2008;Wessel & O'Doherty, 2014;Wessel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%